Lower Cretaceous anoxic conditions IN the Austral basin, south-western Gondwana, Patagonia Argentina - Richiano, Sebastián Miguel (2014)
The reconstruction of palaeo-oxygenation levels in marine deposits from the Cretaceous has obtained a huge interest all around the world in recent years. This fascinating topic is here pointed out for the first time in the Austral Basin using the information provided by the black shales of the Río Mayer Formation, Patagonia, Argentina. The combination of sedimentology, ichnology and geochemistry (TOC, Ce anomaly and MnO content) allow the identification of three major intervals respecting the oxygen content. During the Berriasian and early Valanginian anoxic conditions prevail in the outer shelf. After that, between the late Valanginian and Hauterivian dysoxic palaeoenvironments were developed. Finally, a more oxygenated palaeoenvironment occurred since Aptian associated with a progradation of a proximal deltaic system. The identification of anoxic conditions is of much interest for the hydrocarbon research in this stratigraphical unit, which represents the most significant source rock of the Austral Basin.